Antibody-dependent cellular inhibition is associated with reduced risk against Febrile malaria in a longitudinal cohort study involving Ghanaian children - Tiendrebeogo, R.W.; Adu, B.; Singh, S.K.; Dziegiel, M.H.; Nébié, I.; Sirima, S.B.; Christiansen, M.; Dodoo, D.; Theisen, M. (Open Forum Infectious Diseases, 2015)
The antibody-dependent respiratory burst and opsonic phagocytosis assays have been associated with protection against malaria; however, other mechanisms may also be involved. The antibody-dependent cellular inhibition (ADCI) assay is yet to be correlated with protection in longitudinal cohort studies (LCS). We investigated the relationship between ADCI activity of immunoglobulin G before malaria season and risk of malaria in a LCS involving Ghanaian children. High ADCI activity was significantly associated with reduced risk against malaria. Findings here suggest a potential usefulness of the ADCI assay as a correlate of protection to guide malaria vaccine studies. © The Author 2015. Published by Oxford University Press on behalf of the Infectious Diseases Societyof America.
Keywords: antibody-dependent cellular inhibition; Children; Longitudinal cohort study; Malaria; Monocytes; Plasmodium falciparum